Music Can Create Ambience/Atmosphere in a Restaurant Environment - Mahendra, Gelar; Putra, Gilang Pratama (Universitas Majalengka, 2024)
This study aims to explore the role of music in creating ambience/atmosphere in a restaurant environment. The method used is qualitative by interviewing 15 restaurant visitors in the city of Bandung. The results of the study show that the role of music in the restaurant area has a significant influence in building the desired atmosphere or ambience. Restaurant visitors feel happier when visiting places to eat that play music in their area, because this gives a distinct impression to visitors and increases their satisfaction when enjoying food. Music creates a relaxing and engaging atmosphere, making diners feel entertained and at ease. In contrast, a restaurant without music is boring, only focused on food without a unique impression. This research provides a deeper understanding of the importance of the role of music in creating ambience/atmosphere in a restaurant environment. The implications of this research can be used by restaurant owners to improve visitor experience and expand their customer base. In addition, this research can also be a basis for further research in understanding the influence of music in other environmental contexts.